A LEGAL REVIEW OF THE ROLE OF RELIGIOUS COUNSELORS IN PREMARITAL GUIDANCE TO PROMOTE FAMILY HARMONY AT THE OFFICES OF RELIGIOUS AFFAIRS (KUA) IN TANJUNGPINANG - Hasibuan, Supri Yadin; Salsabila, Salsabila; Halim, Muhammad (Faculty of Law Universitas 17 Augustus 1945 Cirebon, 2025)
This study examines the role of religious counselors in providing premarital guidance at the Offices of Religious Affairs (KUA) in Tanjungpinang City, focusing on its impact on family harmony. The research analyzes how legal frameworks, particularly Law No. 1 of 1974 on Marriage and related regulations, guide counselors in delivering effective premarital counseling. Using a normative-empirical legal research method, the study combines legal analysis of statutory provisions with qualitative field data from interviews and observations. Findings indicate that premarital guidance significantly contributes to marital readiness and communication, but its effectiveness depends on counselors' capacity, methods, and couples' engagement. The study suggests improvements in counselor training, standardized counseling practices, and couples’ legal awareness to enhance the effectiveness of premarital guidance.